Strategi Kementerian Pertahanan dalam Meningkatkan Kesadaran Masyarakat untuk Bergabung dengan Komponen Cadangan dalam Mendukung Pertahanan Nasional - Pratiwi Andini Ristiqomah; Hikmat Zakky Almubaroq; Editha Praditya Duarte (Pusat Riset dan Inovasi Nasional, 2025)
This study explores the strategic efforts of the Indonesian Ministry of Defense to increase public awareness and interest in joining the Reserve Component as part of the Universal People's Defense and Security System (SISHANKAMRATA). Using policy analysis, literature review, and evaluation of communication campaigns, the research examines how outreach strategies—such as media campaigns, educational initiatives, and digital engagement—have impacted public participation. The findings highlight both progress and ongoing challenges, including cultural barriers, inconsistent messaging, and regional disparities. Despite these challenges, efforts to engage the public have yielded some success in raising awareness, though there are still significant gaps in achieving broad participation. The study emphasizes the need for a more coordinated approach to communication, focusing on clear and consistent messaging across regions. It concludes with several policy recommendations aimed at increasing public trust, enhancing outreach effectiveness, and creating sustainable engagement strategies to strengthen the contribution of reserve forces to national defense. These efforts are essential for fostering a well-rounded and resilient defense system in Indonesia.